AB0591 POSITIVE PREDICTIVE VALUE OF THE GIANT CELL ARTERITIS DIAGNOSIS IN THE DANISH NATIONAL PATIENT REGISTRY: A VALIDATION STUDY. (June 2019) - Hjort, Peter; Therkildsen, Philip; Nielsen, Berit Dalsgaard; Hansen, Ib; Thurah, Annette de; Hauge, Ellen-Margrethe
Abstract : Background: Giant cell arteritis (GCA) is the most frequent systemic vasculitis[1]. The diagnosis is clinical and based on symptoms, histopathology, biochemistry and imaging. In Denmark, diagnostic codes for all in- and out-patient hospital diagnoses are registered in the Danish National Patient Registry (DNPR) [2]. Since GCA can be difficult to diagnose and treatment is initiated on suspicion, we hypothesized that the overall positive predictive value (PPV) of the GCA diagnosis code in the DNPR is low. High data quality is important for future epidemiological research in GCA. Objectives: To establish PPV of the diagnostic code of GCA in the DNPR. Furthermore, to identify characteristics associated with a high PPV of the diagnostic code. Methods: 293 patients aged ≥50 years with a first-time register-based GCA diagnosis were included from the DNPR in the period January 2012-January 2018. Patients were sampled based on the ICD-10 codes (M31.5 and M31.6) from two regional hospitals and one university hospital in the Central Region of Denmark. As gold standard we used the medical records (including biochemistry, histopathology and imaging results) and categorized each patient as true GCA or non-GCA. Based on the data from the prescription database, patients were divided into four categories depending on the number of prednisolone prescriptions they received. Two independent investigators (PH and PT) reviewed the medical records. In case of disagreement the final diagnosis was reached by consensus or by expert opinion (ITH). To test how the PPV varied, sub-analyses were performed for number of prescriptions, specific symptoms, temporal artery biopsies (TAB), number of visits and number of prescriptions.. Results: We confirmed 183 of 293 diagnoses resulting in a PPV of 62.8% (95% CI: 57.1-68.2). In patients having at least three admissions, 95 of 110 diagnoses were confirmed (PPV: 86.4%; 95% CI: 78.5-91.7). We confirmed 82 of 95 patients with at least three visits and a TAB. This resulted in a PPV of 86.3% (95% CI: 77.7-91.9). The highest PPV was observed in patients with at least 3 visits and ≥3 prescriptions of prednisolone. In this sub-analysis we confirmed 88 of 95 diagnoses resulting in a PPV of 92.6% (95% CI: 85.2-96.5). Conclusion: This is the first study to validate the diagnostic code of GCA in the DNPR. The overall PPV of a first-time diagnosis of GCA in the DNPR is low. The probability of identifying true cases of GCA increases substantially when diagnostic codes are combined with 3 visits and ≥3 prescriptions of prednisolone. References: [1] Gonzalez-Gay, M.A., et al., Epidemiology of giant cell arteritis and polymyalgia rheumatica. Arthritis Rheum, 2009. 61(10): p. 1454-61. [2] Schmidt, M., et al., The Danish National Patient Registry: a review of content, data quality, and research potential. Clin Epidemiol, 2015. 7: p. 449-90. Acknowledgement: A special thanks to Mette Nørgaard for her help. Disclosure of Interests: None declared